PENGARUH PUPUK FOSFAT DAN PENGATURAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (VIGNA RADIATA L) VIMA 4 - Susanti, Mira Dewi; Jaenudin, Amran; Sungkawa, Iman (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2022)
This experiment aims to determine the effect of phosphate fertilizer on the growth and yield of mung bean (Vigna radiata L.) Vima 4 variety. The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the study was carried out from August to November 2021. The location is located at an altitude of ± 50 m above sea level (masl), the soil type is Latosol. The experimental method used is the experimental method with a Randomized Block Design (RAK), treatment consists of two factors repeated three times. The first factor is the dose of phosphate fertilizer which consists of three levels, namely 50kg/ha, 100kg/ha, 150 kg/ha. While the second factor is the spacing which consists of three levels, namely the spacing of 40cm x 10cm, 40cm x 20cm, and 40cm x 30cm. The main observation data were processed using linear model statistical tests, analysis of variance, and Scott-Knot cluster further test analysis. To find out the correlation between the treatment and the components of the growth and yield of the mung bean, the correlation used is the Product Moment corellation coefficient. The experimental results showed: (1) The combination treatment of phosphate fertilizer dose and spacing had an effect on Leaf Area Index at 14, 28 and 35 DAP, plant growth rate 14-21 DAP and 28-35 DAP, root volumes at 14, 21 and 28 DAP, (2) The combination of 100kg/ha phosphate fertilizer treatment and 40cm x 20 cm spacing gave the best response to the growth and yield of mungbeans (3) There was a significant correlation between plant height and dry seed weight per plot in the 35 DAP observation period with a moderate correlation category, there was a significant correlation between leaf number and dry seed weight per plot at 28 DAP observation period, and there was a significant correlation between root volume and dry seed weight per plot at observation period 35 DAP with weak category.